Abscisic Acid Is a General Negative Regulator of Arabidopsis Axillary Bud Growth. Issue 1 (6th July 2015) - Yao, Chi; Finlayson, Scott A.
Abstract : The plant hormone abscisic acid functions as a general negative regulator of branching and may contribute to the effects of other hormones and proteins that control the process. Abstract: Branching is an important process controlled by intrinsic programs and by environmental signals transduced by a variety of plant hormones. Abscisic acid (ABA ) was previously shown to mediate Arabidopsis ( Arabidopsis thaliana ) branching responses to the ratio of red light (R ) to far-red light (FR ; an indicator of competition) by suppressing bud outgrowth from lower rosette positions under low R :FR . However, the role of ABA in regulating branching more generally was not investigated. This study shows that ABA restricts lower bud outgrowth and promotes correlative inhibition under both high and low R :FR . ABA was elevated in buds exhibiting delayed outgrowth resulting from bud position and low R :FR and decreased in elongating buds. ABA was reduced in lower buds of hyperbranching mutants deficient in auxin signaling (AUXIN RESISTANT1), MORE AXILLARY BRANCHING (MAX) signaling (MAX2), and BRANCHED1 (BRC1) function, and partial suppression of branch elongation in these mutants by exogenous ABA suggested that ABA may act downstream of these components. Bud BRC1 expression was not altered by exogenous ABA, consistent with a downstream function for ABA . However, the expression of genes encoding the indole-3-acetic acid (IAA ) biosynthesis enzyme TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS1, the auxin transporter PIN-FORMED1, and the cell cycle genes CYCLIN A2;1 and PROLIFERATING CELL NUCLEAR ANTIGEN1 in buds was suppressed by ABA, suggesting that it may inhibit bud growth in part by suppressing elements of the cell cycle machinery and bud-autonomous IAA biosynthesis and transport. ABA was found to suppress bud IAA accumulation, thus confirming this aspect of its action.